PERBEDAAN MORDAN JERUK BALI (Citrus Maxima Merr) dan JERUK LEMON (Citrus Limon) TERHADAP HASIL PENCELUPAN BAHAN SUTERA MENGGUNAKAN EKSTRAK KELOPAK BUNGA PISANG RAJA (Musa Sapientum) - Anggraeni, Anisa; Adriani, Adriani; Novrita, Sri Zulfia (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This event will be based on research in an effort to revive the image of theuse of the substance is natural color. The addition of mordan on its substance isnatural color will affect the color of the immersion. This study aims to describethe name of the color (hue), dark bright colors (value), color, and differences inflatness mordan Pomelo (Citrus Maxima Merr) and Lemon (Citrus Limon)against the results of dyeing Silk material using extracts of flower petals Plantain(Musa Sapientum). This type of research is a research experiment. The data used2are sourced from 18 person panelists, then analyzed using Friedman's test k-Related samples or ANOVA of one line. Immersion results without mordanproduce color Clam Shell Pink #C5A89B, with value categories very bright andkerataaan colors on the category very flat. mordan Pomelo produce color DarkSalmon Pink #B59890 with value are bright enough and kerataaan colors are flat,whereas with mordan Lemon is Warm Brown #AE8C8B with value are brightenough and kerataaan colors are blended. The results of the data analysis of darklight color (value) is 0.002 < 0.05, then H0 is rejected, meaning that there is adifference significant color light dark. As for the flatness of the color dataobtained is 0.154 > 0.05 H0 is accepted, then this means that there is nosignificant difference in color of the flatness on dyeing silk material usingPlantain flowers petals extract with Grapefruit and mordan mordan LemonKata kunci: Perbedaan Mordan, Bunga Pisang Raja